PRICE VOLATILITY ANALYSIS OF CAYENNE PEPPER (Capsicum frutescens) IN EAST JAVA - Aisyah Mandarsari; Ratya Anindita; Setiawan Budi (Socio-Economics/Agribusiness Department, 2020)
The fluctuations in the price of cayenne are still a problem that continues to occur throughout the year. In certain seasons, the increase in the price of cayenne is quite significant, affecting the rate of increase. The government continues to approve and implement the stabilization policy for cayenne prices. In line with this, this study offers to examine the volatility of cayenne prices both at the producer level and at the consumer level. In the research also analysis of spillover volatility to study the presence or absence of transmission volatility that occurs in the price of cayenne at the consumer level and prices at the producer level. The method used in this study is ARCH / GARCH and GARCH-BEKK. The results show that price volatility at the producer level is high volatility, while price volatility at the consumer level shows a higher value is extreme volatility. The results of this study also show the fact that there is volatility in the price of cayenne at the consumer level with the price of cayenne at the producer level. Information about the results of this study is expected to help stabilize the price of cayenne in the market.